Penggunaan teknik jigsaw dalam meningkatkan tahap penguasaan penyelesaian masalah Fizik - Florita @ Nurul Awatif, Laji (2010)
The purpose of this study is examine whether the jigsaw technique used in teaching and learning could increase student' ability to solve problem in physic subject. This study compared two methods of teaching-the conventional the jigsaw technique. Thirty two students from a rural school in Kota Kinabalu were used as subjects. They were divided into control-group (normal lesson) and treatment-group (using jigsaw technique) in a quasi experiment method. This study intends to make the subject of physics as an interesting subject matter hr students to explore by maximizing their level of understanding through the sharing of knowledge and information among them. Learning in classes may not only be obtained from black board and teachers, but it is an unlimited and borderless discovery process of knowedge and information. The findings were analyzed using descriptive statistics in determining the mean score of students' achievements, and the paired t-test to examine significant scores gathered from the two groups. Findings showed that students in the treatment-group (who use jigsaw technique) demonstrated an increase in their level of undestanding from weak to excellent, and the significant difference between the two groups at a confidence level of more than 95%, p<.05. Based on the study and summary made, it can be concluded that the group that used the jigsaw technique is more effective compared to the group that only used conventional teaching. This means that the delivery of physics information and the ability of student to solve any problems solving can be increased through the discovery method. Hence, knowledge acquired by students can be sustained longer in their minds. Some important recommendations were given based on the findings